Coronary computed tomography angiography in coronary artery disease: a systematic review of image quality, diagnostic value and radiation dose. - Sun, Zhonghua (Nova Publishers, 2013)
Coronary artery disease is the leading cause of death in the developed countries of the world and it is becoming increasingly common in the developing world. Conventional invasive coronary angiography currently remains the gold standard for the evaluation of patients with known or suspected coronary artery disease. Limitations of the modality include its invasiveness, expense and time consumption, with small but substantial procedure-related complications. In recent years, systematic reviews and meta-analyses of the diagnostic value of coronary CT angiography are increasingly being used to measure the progress and innovations in the diagnostic management of patients with suspected coronary artery disease. This book provides an overview of the scientific methods used to search, analyze, appraise and synthesize studies on coronary CT angiography.